Relativas livres e interrogativas parciais: paralelos e diferenças - Matos, Gabriela; Brito, Ana Maria (Revista da Associação Portuguesa de Linguística, 2018)
In this paper we analyse parallelisms and differences between free relatives, true embedded wh interrogatives, and improper embedded wh interrogatives. While free relatives are DPs which contain a CP, embedded wh interrogatives, both true and improper interrogatives, are CPs. In the last years and in the framework of the Minimalist Program, this different categorial nature has been deduced from formal labelling conditions, mainly related to the nature of head or maximal projection of the moved wh constituent. In this paper, while not rejecting the importance of the difference between head and maximal projection of the wh constituent, we show that the DP or CP nature of the embedded constituent and its [+int] or [+decl] status must be sanctioned by the selection requirements of the matrix predicate.